Tax Reform Effect on Local Tax Buoyancy in Indonesia - Riyath Iskandar; Srinita Srinita; Putri Bintusy Syathi (Research Collaboration Community (RCC), 2021)
This study analyzes local tax efforts through the buoyancy rate method in 423 regions consisting of 341 Regency Governments and 82 City Governments in Indonesia for the period 2007 to 2019, using the panel data regression method with a fixed effect model. The research shows that changes in regional taxation policies with Law of Republic Indonesia Number 28 year 2009 concerning Local Taxes and Charges have a positive impact on efforts to collect Local Taxes with a significant increase in the value of the regional tax buoyancy rate. The value of the local tax buoyancy rate obtained is higher for the City Government than for the Regency Government, so it is necessary to adjust regional tax policies consistently to overcome the inequality of income realization that occurs between the Regency and City Governments in order to increase regional fiscal independence.